Plasma assisted design of biocompatible 3D printed PCL/silver nanoparticle scaffolds: in vitro and in vivo analyses. Issue 20 (17th September 2021) - Ninan, Neethu; Joseph, Blessy; Visalakshan, Rahul Madathiparambil; Bright, Richard; Denoual, Clement; Zilm, Peter; Dalvi, Yogesh Bharat; Priya, P. V.; Mathew, Aji; Grohens, Yves; Kalarikkal, Nandakumar; Vasilev, Krasimir; et al.
Abstract : 3D printing provides numerous opportunities for designing tissue engineering constructs with intricate porosity, geometry and favourable mechanical properties and has the potential to revolutionize medical treatments. Abstract : 3D printing provides numerous opportunities for designing tissue engineering constructs with intricate porosity, geometry and favourable mechanical properties and has the potential to revolutionize medical treatments. However, an often-encountered restriction is the selection of materials suitable for utilization in 3D printing, not all of which have appropriate biocompatibility properties. In this work, fused deposition modeling was employed to fabricate 3D PCL constructs without the use of any solvent. Plasma deposition was used to modify the surface of the scaffolds, followed by immobilization of silver nanoparticles. The physico-chemical and mechanical analyses demonstrated that the scaffolds retained their porosity and mechanical integrity. The mechanical properties evaluated by the nanoindentation technique demonstrated an increase in reduced modulus to 1.87 ± 0.012 GPa for PCL scaffolds functionalized with silver nanoparticles for 24 hours. We also showed complete prevention of colonization by medically relevant pathogens. The modified scaffolds had good biocompatibility. The immune response studies in the culture of macrophages confirmed a reduction in the level of expression of pro-inflammatory cytokines which is a key requirement for successful wound healing. The in vivo studies on Sprague Dawley rats indicated enhanced angiogenesis and the absence of foreign body reaction for scaffolds functionalized with silver nanoparticles for 6 hours. The 3D printing approach presented in this study provides new sustainable opportunities that can be adopted for designing biomaterial constructs with enhanced biological properties.